Odpowiedź :
2x-y=10
x+5y=-17
y= 2x-10
x+5(2x-10)=-17
x+10x-50=-17
11x=33
x=3
y=2*3-10
x=3
y=-4
x=3
x+5y=-17
y= 2x-10
x+5(2x-10)=-17
x+10x-50=-17
11x=33
x=3
y=2*3-10
x=3
y=-4
x=3
2x-y=10
x+5y=-17
-y=10 -2x |* (-1)
x+5y=-17
y=-10+ 2x
x+5(-10+2x)=-17
y=-10+ 2x
x-50+ 10x=-17
y=-10+ 2x
x+10x = -17 +50
y=-10+ 2x
11x = 33 / 11
y=-10+ 2x
x=3
y=-10+2*3
x=3
y= (-4)
x=3
Pozdrowienia liczę na max >D !
x+5y=-17
-y=10 -2x |* (-1)
x+5y=-17
y=-10+ 2x
x+5(-10+2x)=-17
y=-10+ 2x
x-50+ 10x=-17
y=-10+ 2x
x+10x = -17 +50
y=-10+ 2x
11x = 33 / 11
y=-10+ 2x
x=3
y=-10+2*3
x=3
y= (-4)
x=3
Pozdrowienia liczę na max >D !
2x-y=10
x+5y=-17 /-5y
2x-y=10
x=-17-2y
2(-17-2y)-y=10
x=-17-2y
-34-4y -y=10 /+34
x=-17-2y
-5y=44 |:-5
x=-17-2y
y=-44/5
x=-17-2y
y=-44/5
x=-17-2*-44/5
y=-44/5
x=-17+88/5 = -17+17 i 3/5
y=-8,8
x=0,6
x+5y=-17 /-5y
2x-y=10
x=-17-2y
2(-17-2y)-y=10
x=-17-2y
-34-4y -y=10 /+34
x=-17-2y
-5y=44 |:-5
x=-17-2y
y=-44/5
x=-17-2y
y=-44/5
x=-17-2*-44/5
y=-44/5
x=-17+88/5 = -17+17 i 3/5
y=-8,8
x=0,6